High-Throughput Selection of Effective RNAi Probes for Gene Silencing - Kumar, Rajeev (Cold Spring Harbor Laboratory Press, 2003)
RNA interference (RNAi) is a process of sequence-specific posttranscriptional gene silencing mediated by double-stranded RNA. RNAi has recently emerged as a powerful genetic tool to analyze gene function in mammalian cells. The power of this method is limited however, by the uncertainty in predicting the efficacy of small interfering RNAs (siRNAs) in silencing a gene. This has imposed serious limitations not only for small-scale but also for high-throughput RNAi screening initiatives in mammalian systems. We have developed a reliable and quantitative approach for the rapid and efficient identification of the most effective siRNA against any gene. The efficacy of siRNA sequences is monitored by their ability to reduce the expression of cognate target-reporter fusions with easily quantified readouts. Finally, using micro array-based cell transfections, we demonstrate an unlimited potential of this approach in high-throughput screens for identifying effective siRNA probes for silencing genes in mammalian systems. This approach is likely to have implications in the use of RNAi as a reverse genetic tool for analyzing mammalian gene function on a genome-wide scale.